Eigenvalues of non linear problems lectures given at the Centro internazionale matematico estivo (C.I.M.E.) held in Varenna (Como), Italy, June 16-25, 1974 - C.I.M.E. Summer School Varenna, Italy) (1974; Prodi, G. 1925- (Giovanni).; SpringerLink (Online service). (Berlin London Springer, 2010)
H. Amann: Nonlinear eigenvalue problems in ordered Banach spaces.- P.C. Fife: Branching phenomena in fluid dynamics and chemical reaction-diffusion theory.- W. Klingenberg: The theory of closed geodesics.- P. Rabinowitz: Variational methods for nonlinear eigenvalue problems.- M. Reeken: Existence of solutions to the Hartree-Fock equations.- R. Turner: Positive solutions of nonlinear eigenvalue problems.
H. Amann: Nonlinear eigenvalue problems in ordered Banach spaces -- P.C. Fife: Branching phenomena in fluid dynamics and chemical reaction-diffusion theory -- W. Klingenberg: The theory of closed geodesics -- P. Rabinowitz: Variational methods for nonlinear eigenvalue problems -- M. Reeken: Existence of solutions to the Hartree-Fock equations -- R. Turner: Positive solutions of nonlinear eigenvalue problems.
Electronic reproduction.
Keywords: Differential equations, Partial -- Congresses; Nonlinear theories -- Congresses; Eigenvalues -- Congresses; Electronic books